Doing Theology in the Wake of Genocide: “Can Our Theology Ever be the Same Again After [Gaza]?” - Klassen, Marie-Claire (Journal of the Society of Christian Ethics, 2025)
What does it mean to do theology amid the genocide in Gaza? This essay responds to this question, beginning with a similar concern posed by Johann Baptist Metz after the Holocaust: Can our theology ever be the same again after Auschwitz? Metz’s theological response, which includes turning to the “dangerous memory” of the oppressed and calling for costly solidarity, provides a starting point but ultimately proves insufficient. His post-Holocaust theology fails to recognize the “dangerous memories” of Palestinians. This essay critically engages both post-Holocaust theology and Christian Zionism, demonstrating how both theologies are complicit in the violence unfolding in Palestine-Israel today. Utilizing resources from Palestinian liberation theology and Bashir Bashir and Amos Goldberg’s work, which brings memories of Nakba and Holocaust together as part of a shared history, this essay proposes a Christian theological approach that takes accountability for Christian complicity in both anti-Palestinian racism and antisemitism.